Experimental Investigation of Water-Rich Fully Weathered Granite on Water Bursting and Mud Bursting - Zheng, Suping (Frontiers in Earth Science, 2021)
In order to investigate the mechanism of water-rich and fully weathered granite on the water bursting and mud bursting, the single-factor variable method is adopted in this study. The particle size gradation, initial porosity, water pressure, confining pressure, and anti-outburst thickness are chosen to determine each factor on the evolution of sand gushing, porosity, permeability, fine particle concentration, and water gushing velocity. Results indicate that a particle loss is the most critical reason for the water bursting and mud bursting of water-rich and fully weathered granite. The transition of water bursting from the linear to the nonlinear stage is the most significant feature. Soil particles with a larger Talbol power index are more likely to lead to water bursting. In addition, there is a critical water pressure to control the occurrence of water bursting and mud bursting. It is found that when the confining pressure reached the soil yield strength, the evolution of water bursting and mud bursting is independent of the increase in confining pressure. The increase in anti-outburst thickness can also effectively limit the risk of water bursting and mud bursting.